2023
DOI: 10.1001/jamanetworkopen.2023.18919
|View full text |Cite
|
Sign up to set email alerts
|

Findings From the World Mental Health Surveys of Civil Violence Exposure and Its Association With Subsequent Onset and Persistence of Mental Disorders

Abstract: ImportanceUnderstanding the association of civil violence with mental disorders is important for developing effective postconflict recovery policies.ObjectiveTo estimate the association between exposure to civil violence and the subsequent onset and persistence of common mental disorders (in the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition [DSM-IV]) in representative surveys of civilians from countries that have experienced civil violence since World War II.Design, Setting, and Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Our findings on how exposure to violence in combat and the experience of assault are associated with health outcomes complement existing research. For example, Axinn et al (2023) found, that exposure to civil violence in 7 countries that experienced civil violence since WWII, was associated with a higher risk of mental disorders in the long term [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings on how exposure to violence in combat and the experience of assault are associated with health outcomes complement existing research. For example, Axinn et al (2023) found, that exposure to civil violence in 7 countries that experienced civil violence since WWII, was associated with a higher risk of mental disorders in the long term [28].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings on how exposure to violence in combat and the experience of assault are associated with health outcomes complement existing research. For example, Axinn et al (2023) found, that exposure to civil violence in 7 countries that experienced civil violence since WWII, was associated with a higher risk of mental disorders in the long term [ 28 ]. Similarly, in a study of U.S.-based WWII and Korean War veterans, Elder and Chipp (1989) found that heavy combat veterans were at higher risk for emotional and behavioral problems, compared with noncombat and light combat veterans [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings on how exposure to violence in combat and the experience of assault are associated with health outcomes complement existing research. For example, Axinn et al (2023) found, that exposure to civil violence in 7 countries that experienced civil violence since WWII, was associated with a higher risk of mental disorders in the long term [28].…”
Section: Discussionmentioning
confidence: 99%
“…As people enter adulthood, their experiences and exposures to new adverse events can also have long-term impacts. Exposure to adversity across the life course has the potential to profoundly impact cognitive, mental, and physical health [8,9,[25][26][27][28][29]. For example, having a close relative who is addicted to drugs or alcohol has been found to have lasting effects on an individual's emotional well-being, often through stress and family strain [30,31].…”
Section: Introductionmentioning
confidence: 99%